Economic growth and development - "Pal, Prankrishna (ed.)" (New Delhi, 2007)
Economic Growth and Development : Emerging Issues is an edited volume based on papers presented at a UGC sponsored seminar organized by the Department of Economics, Rabindra Bharati University and invited papers from the distinguished scholars. Thematically these papers are arranged into five sections: (1) Growth and Development: General Issues, (ii) Primary Sector, (iii) Financial Sector, (iv) Social Sector, and (v) Trade Related Issues.
Keywords: Economic development